Clinical implications of synovial tissue phenotypes in rheumatoid arthritis - Bykerk, Vivian P. (Frontiers in Medicine, 2024)
Autoimmune forms of inflammatory arthritis, such as Rheumatoid Arthritis (RA) are clinically heterogeneous in presentation and disease course. Treatment-related outcomes vary, despite patient exposure to similar treatment strategies. Synovial heterogeneity is likely influenced by multiple clinical and patient factors, including environmental exposures, microbiota, behaviors, and timely access to therapy, which affect the synovial endotype (AKA pathotype) expression during RA pathogenesis. Each patient's set of unique complex factors manifests with specific synovial pathotypes characterized by clusters of synovial cell types and states. Precision medicine aims to use such clinical and biological data to identify the right treatment for the right patient at the right time enabling patients to achieve sustained remission. (1) Identifying synovial targets in a given pathotype, susceptible to a given treatment enabling the choice of effective therapy for a given patient, will advance the goals of precision medicine, where patients can be treated with the right therapy at the right time. Over the last 7 years, improved acquisition and processing of synovial tissue obtained by ultra-sound guided synovial biopsy has enabled researchers to define and refine synovial pathotypes using histologic features and predominant cell types that are associated with clinical manifestations. Technical advances have enabled single-cell simultaneous sequencing of proteins and gene expression to generate exponential increases in transcriptomic data. Increasingly sophisticated bioinformatic methods have been applied to heterogeneous data to identify diverse and novel cell types and states that cluster in the RA synovium to define patient subgroups. Newly identified synovial pathotypes and endotypes are now being integrated into clinical studies and trials to explain clinical heterogeneity in the disease course and understand treatment response. Rapidly evolving clinical-translational research has linked an expanded understanding of RA synovial pathogenesis that can be linked with clinically meaningful subgroups and treatment outcomes to disentangle the clinical heterogeneity in RA.